Aspergillosis, avian species and the one health perspective : the possible importance of birds in azole resistance - Melo, Aryse Martins (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (http://creativecommons.org/licenses/by/4.0/).